Penyuluhan tentang Common Cold dan Pijat Common Cold dalam Upaya Mengatasi Gejala Batuk Pilek pada Bayi/Balita - Annisa Mastri Wahyu Nurjati; Icca Oktavia Noor Hidayati; Rinawati; Luvi Dian Afriyani (Universitas Ngudi Waluyo, 2026)
The common cold is an upper respiratory tract infection that frequently affects infants and toddlers. A situation analysis in Pringsari Village, Pringapus District, Semarang Regency, found a high incidence of coughs and colds in infants and toddlers, as well as low maternal knowledge regarding non-pharmacological treatment, such as common cold massage. Therefore, this community service program aims to improve mothers' knowledge and skills in performing common cold massage to address cough and cold symptoms in infants and toddlers. Babies are weak individuals and require an adaptation process. Every baby must be able to go through a physiological adaptation process consisting of the cardiovascular, respiratory system, hematopoiesis system, metabolism, body temperature, digestive tract system, endocrine glands, immunoglobulin system, glucose metabolism, integumentary and reproductive systems. Performing a Common Cold massage consisting of stages of massage for babies with coughs and colds consisting of the following movements: toward bridge nose & under the cheekbone, cheek rain drop, open book, butterfly, toby top intercostal, chest rain drop, positioning the baby face down, back and forth, sweeping neck to bottom, sweeping neck to feet, back circle, back rain drop, pitching and relaxation. Counseling on Common Cold Massage for Babies and Toddlers as an Effort to Overcome Coughs and Colds in the Pringsari Village Area, Pringapus District, Semarang Regency, which was attended by 15 respondents who were mothers who had babies. The Community Service Implementation was carried out on Saturday, May 9, 2026, starting at 09.00 – 11.30 WIB offline, with a method with an introduction first, then filling out the pre-test, then the presentation of the material and continued with a demonstration of Common Cold massage with 13 stages, followed by a question and answer process, then filling out the post-test and finally closing. The counseling participants understood and comprehended how to do Common Cold Massage to Overcome Coughs and Colds in Babies and Toddlers and good communication was established between the proposing team and the mothers who conducted the counseling. There was an increase in the knowledge and skills of mothers, as seen from the good percentage data of 53.3% (pretest) to 93.3% (posttest). It is hoped that mothers can practice Common Cold massage at home independently when their children have coughs and colds. Abstrak Common cold merupakan salah satu gangguan saluran pernapasan atas yang sering terjadi pada bayi dan balita. Berdasarkan hasil analisis situasi di Desa Pringsari, Kecamatan Pringapus, Kabupaten Semarang, ditemukan masih tingginya kejadian batuk pilek pada bayi dan balita serta rendahnya pengetahuan ibu mengenai penanganan nonfarmakologis berupa pijat Common Cold. Oleh karena itu, pengabdian masyarakat ini dilakukan untuk meningkatkan pengetahuan dan keterampilan ibu dalam melakukan pijat Common Cold sebagai upaya mengatasi gejala batuk pilek pada bayi dan balita. Bayi merupakan individu yang lemah dan memerlukan proses adaptasi. Setiap bayi harus dapat melalui proses adaptasi fisiologis yang terdiri dari kardiovaskuler, sistem pernafasan, sistem hematopoiesis, metabolisme, suhu tubuh, sistem traktus digestivus, kelenjar endokrin, sistem imunoglobulin, metabolisme glukosa, sistem integumen dan reproduksi. Melakukan pijat Common Cold yang terdiri dari tahapan pijat bayi batuk pilek yang terdiri dari gerakan berikut melakukan gerakan toward bridge nose & under the cheek bone, cheek rain drop, open book, butterfly, toby top intercostal, chest rain drop, memposisikan bayi telungkup, back and forth, sweeping neck to bottom, sweeping neck to feet, back circle, back rain drop, pitching dan relaksasi. Penyuluhan Pijat Common Cold Pada Bayi dan Balita Sebagai Upaya Mengatasi Batuk Pilek di Wilayah Desa Pringsari, Kecamatan Pringapus, Kabupaten Semarang yang diikuti oleh 15 responden Ibu yang memiliki bayi. Pelaksanaan Pengabdian Masyarakat dilakukan Hari Sabtu, 9 Mei 2026 mulai pukul 09.00 – 11.30 WIB secara luring (offline), dengan metode dengan perkenalan terlebih dahulu selanjutnya pengisian Pre Test, kemudian pemaparan materi dan dilanjutkan demonstrasi pijat Common Cold dengan 13 tahapan, berikutnya proses tanya jawab kemudian pengisian Post Test dan terakhir penutup. Peserta penyuluhan mengerti dan memahami cara melakukan Pijat Common Cold Untuk Mengatasi Batuk Pilek pada Bayi dan Balita dan bisa terjalin komunikasi baik tim pengusul dan para ibu yang melakukan penyuluhan. Terdapat peningkatan pengetahuan dan keterampilan ibu-ibu, yang dilihat dari data presentase baik 53,3% (pretest) menjadi 93,3% (Post Test). Diharapkan ibu-ibu dapat mempraktikkan pijat Common Cold dirumah secara mandiri saat anaknya mengalami batuk dan pilek.